Development and status of vehicular ad hoc networks - CHANG Cu-yu; XIANG Yong; SHI Mei-lin (Tongxin xuebao)
Historical development,characteristics and application fields of vehicular ad hoc networks（VANET） were in-troduced briefly.The advantages and disadvantages were discussed with analysis and comparison if various classes of MAC and routing protocol were applied to VANET.According to the characteristics of VANET,the ideas and break-through direction of inter-vehicle communication design of VANET were proposed.The active research institute and their main works about VANET were introduced to convenient the reader for tracking advanced research achievement at abroad.